The Development of Mental Discipline Theory in Islamic Religious Education Learning - Arlis Karlina; Komarudin Sassi (CV. Creative Tugu Pena, 2025)
Islamic religious education plays a crucial role in shaping students’ character, particularly when introduced at an early age, a developmental stage in which children learn by observing and imitating those around them. This study employs a qualitative research method, focusing on descriptive analysis of written sources. The primary approach used is library research, involving the review, examination, and interpretation of books and scholarly writings relevant to Islamic character formation in educational settings. The findings indicate that character development aligned with Islamic values—such as religiosity, honesty, discipline, independence, and responsibility—is essential for preparing students to become individuals who contribute positively to society, the nation, and the state. The study reveals that instilling Islamic character values early in a child’s life significantly influences their moral, behavioral, and social development in later years. Early exposure provides a strong foundation for internalizing ethical principles, promoting consistent moral behavior, and supporting the formation of a well-rounded Muslim identity. Overall, this research underscores the importance of early Islamic character education as a transformative effort that impacts students’ long-term development. It highlights the need for structured, value-based educational practices to cultivate future generations with strong moral integrity and social responsibility.